Equality Law Protection for Legal Education: Internships, Volunteering and Clinics - Alysia Blackham (Legal Education Review)
‘Practical’ legal education offers significant educational and personal benefits. However, it also comes with risks that need to be actively managed, including the risk of students experiencing harassment and discrimination. This article considers the scope of equality law, and how it applies to different forms of ‘practical’ legal education activities. It considers how equality law applies to ‘volunteer’ positions, including those in law firm partnerships, barristers’ chambers, and community organisations, legal internships and law school-run legal clinics. It considers the complexity of the legal framework, and the resulting difficulties law students might have in asserting their equality rights. It argues there is a particular need to address three gaps in the current legal framework for practical legal education activities, by: adopting a broader definition of ‘work’ to include unpaid roles; regulating harassment on grounds other than sex; and protecting law students from the actions of third parties, such as clients and members of the public.